(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This research looked at how big data analytics is incorporated into Academic libraries’ decision-making processes, with a focus on how it may improve evidence-based management, service delivery, and strategic planning. The study used a mixed-method approach to support a descriptive and analytical research design and was carried out among Academic libraries in Chennai, India. Using structured questionnaires and pertinent secondary sources, information was gathered from 120 library professionals employed at Academic, deemed institutions, and affiliated colleges. The results showed that library professionals had a moderate to high level of understanding of big data analytics, with circulation data, user attendance records, and electronic resource consumption statistics being important data sources. Major decision-making domains including budget allocation, user service enhancement, subscription administration, and collection creation were greatly aided by big data analytics. Notwithstanding these advantages, obstacles such a lack of technical expertise, poor infrastructure, a lack of funding, and worries about data security and privacy made adoption difficult. All things considered, the research demonstrated the increasing significance of big data analytics as a tactical instrument for enhancing decision quality and coordinating academic library services with user requirements and institutional goals.